PENINGKATAN KEMAMPUAN WIRAUSAHA MELALUI PENDIDIKAN JAHIT DAN BORDIR PADA PANTI ASUHAN AL-HUSNA DI LANDUNGSARI KECAMATAN DAU KABUPATEN MALANG (UPGRADES ENTREPRENEURSHIP THROUGH EDUCATION SEWING AND EMBROIDERY AT ORPHANAGE AL-HUSNA IN LANDUNGSARI SUBDISTRICT DAU MALANG) - Soelistyo, Aris (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Malang, 2016)
The Qur'an insists on the importance of care for orphans, thepoor and helping others in various fields. Orphanage AlHusna Malang, the vision and mission based on concern forthe orphans and the poor. A number of programs to helporphans, orphans and dhu'afa. The program was conducted onthe educational, social and religious. Al-Husna FoundationProgram includes six courses that regular donors program,the movement of the foster parents' caring school